2013
DOI: 10.1158/0008-5472.can-12-4174
|View full text |Cite
|
Sign up to set email alerts
|

OX40 Is a Potent Immune-Stimulating Target in Late-Stage Cancer Patients

Abstract: OX40 is a potent co-stimulatory receptor that can potentiate T cell receptor signaling on the surface of T lymphocytes, leading to their activation by a specifically recognized antigen. In particular, OX40 engagement by ligands present on dendritic cells dramatically increases the proliferation, effector function and survival of T cells. Preclinical studies have shown that OX40 agonists increase anti-tumor immunity and improve tumor-free survival. In this study, we performed a Phase I clinical trial using a mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
311
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(327 citation statements)
references
References 37 publications
8
311
0
8
Order By: Relevance
“…55,56 A phase I study performed in melanoma patients with anti-OX40 mouse monoclonal antibody confirmed its potent antitumor property. 57 It is interesting to combine coinhibitory inhibitors and costimulatory factors to completely activate the anergic T cells in tumors. Previous studies showed that PD-1 blockade and OX40 agonist jointly yield tumor rejection 58 but no clinical trials are available in NSCLC so far.…”
Section: Combination Strategiesmentioning
confidence: 99%
“…55,56 A phase I study performed in melanoma patients with anti-OX40 mouse monoclonal antibody confirmed its potent antitumor property. 57 It is interesting to combine coinhibitory inhibitors and costimulatory factors to completely activate the anergic T cells in tumors. Previous studies showed that PD-1 blockade and OX40 agonist jointly yield tumor rejection 58 but no clinical trials are available in NSCLC so far.…”
Section: Combination Strategiesmentioning
confidence: 99%
“…The OX40 receptor is inducible on activated T cells (11-15) and its engagement with cognate ligand or agonistic antibody enhances T-cell proliferation, cytokine production, survival, and memory development (16,17). In animal models, anti-OX40 has shown favorable antitumor activities and in autoimmune models increases the severity of disease (18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…OX40 is a receptor found on CD4+ and CD8+ T cells, and its engagement helps promote T cell activation, proliferation and cytokine production. These class of agents is still in its early stage, and needs more clinical investigation [12].…”
Section: Discussionmentioning
confidence: 99%